2011
DOI: 10.1002/prot.23145
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of electrostatic interactions in the denatured state ensemble of the N‐terminal domain of L9 under native conditions

Abstract: The pH dependence of protein stability is defined by the difference in the number of protons bound to the folded state and to the denatured state ensemble (DSE) as a function of pH. In many cases, the protonation behavior can be described as the sum of a set of independently titrating residues; in this case, the pH dependence of stability reflects differences in folded and DSE pK(a)'s. pH dependent stability studies have shown that there are energetically important interactions involving charged residues in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 89 publications
1
29
0
Order By: Relevance
“…Mutation of these residues to alanine destabilizes the domain significantly, and the DSE of the double mutant is ∼70% populated at 12°C and pH 5.5, with two sets of resonances observed in the HSQC spectrum. 40 pH jump fluorescence-monitored stopped-flow measurements were used to directly determine the rate of exchange between the folded state and DSE. The exchange rate (k ex = k fold + k unfold ) is 15.7 s −1 , confirming that the system is in slow exchange on the NMR chemical shift time scale ( Figure S1 of the Supporting Information).…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutation of these residues to alanine destabilizes the domain significantly, and the DSE of the double mutant is ∼70% populated at 12°C and pH 5.5, with two sets of resonances observed in the HSQC spectrum. 40 pH jump fluorescence-monitored stopped-flow measurements were used to directly determine the rate of exchange between the folded state and DSE. The exchange rate (k ex = k fold + k unfold ) is 15.7 s −1 , confirming that the system is in slow exchange on the NMR chemical shift time scale ( Figure S1 of the Supporting Information).…”
Section: ■ Resultsmentioning
confidence: 99%
“…These observations are consistent with our previous hydrodynamic measurements of the DSE of V3A/I4A-NTL9 in native buffer and in different concentrations of urea, which showed that the DSE is compact in native buffer and becomes more extended in urea. 40 The secondary shift analysis shows that there is substantial α-helical propensity in the DSE of V3A/I4A-NTL9 populated in buffer. It is natural to inquire about the origin of these propensities and to ask whether the residual secondary structure is native-like or non-native-like, and if it is stabilized by local interactions.…”
Section: ■ Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The probability for the distance to be within 5 Å (defined here as an ion contact) is generally <10%, whereas the probability for the distance to be within 8 Å is no more than 30%. Second, no significant differences are found between the distributions for NTL9 and NTL9 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), suggesting that the presence of the b-sheet segments (residues 1-5 and [18][19][20][21][22] has no influence on the electrostatic interactions. Also, the distributions for the b-hairpin and unstructured states of NTL9 are similar, further suggesting the lack of correlation between electrostatic interactions and b-sheet formation.…”
Section: Individual Ion-pair Interactions Are Weak and Not Correlatedmentioning
confidence: 94%
“…It was found that even though both fragments are unstructured, the pK a of Asp 8 is shifted lower than the model value (4.0) by 0.16 and 0.34 units, respectively (13,14). Interestingly, these shifts are slightly smaller than the pK a of Asp 8 in a destabilizing mutant, V3AI4A, which was estimated to be 0.44 units (21). The observation that the pK a of Asp 8 is slightly depressed in NTL9 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) suggests the presence of other attractive interactions in addition to Lys 12 , and raises the question about specificity of electrostatic interactions in the unfolded state.…”
Section: Introductionmentioning
confidence: 90%